Evaluation of antifungal and anti-aflatoxigenic properties of non-aflatoxigenic Aspergillus flavus strains’ crude extracts against aflatoxigenic A. flavus in peanut kernels - Rahman, Mohd Azuar Hamizan; Samsudin, Nik Iskandar Putra; Sanny, Maimunah; Shaari, Khozirah; Ahmad, Syahida; Selamat, Jinap; Mahror, Norlia; Lim, Wei Ern; Anandan, Visnupreya; Zainaldin, Muhammad Alif (2024)
Peanuts (Arachis hypogaea L.) are highly susceptible to Aspergillus flavus colonisation and aflatoxin contamination. As an alternative to chemically synthesised fungicides, biological control agent using non-aflatoxigenic A. flavus have been developed and commercialised on the basis of nutrient and habitat competition against its aflatoxigenic counterpart. At present, there are interests in harnessing the inhibitory metabolites from non-aflatoxigenic A. flavus. From our previous studies, the crude extract of ethyl acetate and hexane from non-aflatoxigenic A. flavus strain A121R inhibited 100% of aflatoxigenic A. flavus strain A8R growth and AFB1 in vitro at 75 mg/mL. Therefore, the present work aimed to evaluate the antifungal properties of hexane and ethyl acetate crude extracts from non-aflatoxigenic A. flavus A121R against aflatoxigenic A. flavus A8R growth and AFB1 production on peanut kernels. A total of ten concentrations were prepared (150 mg/mL, 75 mg/mL, 35 mg/mL, 18.75 mg/mL, 9.38 mg/mL, 4.69 mg/mL, 2.34 mg/mL 1.17 mg/mL, 0.58 mg/mL, and 0.29 mg/mL). The antifungal properties of crude extracts were assessed by observing fungal growth on the treated peanut kernels for 7 d. On day 3, peanut kernels treated with 150 mg/mL of ethyl acetate crude extract showed aflatoxigenic A. flavus A8R growth, which sporulated on day 5. However, no sign of fungal growth was observed after 7 d of incubation on peanut kernels coated with 150 mg/mL of hexane crude extract. The anti-aflatoxigenic properties of the crude extracts were evaluated by HPLC against control (growth on untreated peanut kernels). The highest inhibition of ethyl acetate crude extract was 54% at 150 mg/mL, and the lowest was 41% at 2.34 mg/mL. No significant AFB1 inhibition was observed at 1.17 mg/mL, 0.58 mg/mL, and 0.29 mg/mL of ethyl acetate crude extract. On the contrary, no AFB1 was detected on peanut kernels treated with 150 mg/mL of hexane crude extract (100% inhibition). The hexane crude extract inhibited more than 90% of AFB1 on peanut kernels treated with 75 mg/mL to 18 mg/mL, and 21% at 0.58 mg/mL. Therefore, hexane crude extract of non-aflatoxigenic A. flavus strain A121R showed promising bioactivity against aflatoxigenic A. flavus strain A8R growth and AFB1 production.